Perancangan Ulang Favehotel Gatot Subroto Jakarta Dengan Pendekatan Brand Identity - Thalita Haryanto, Anastasya; Salayanti, Santi; Murdowo, Djoko (Telkom University, 2024)
FaveHotel Gatot Subroto Jakarta is a 3-star hotel located on Jl. Gatot Subroto, Jakarta. This hotel provides rest areas for guests who travel or activities in Jakarta. Facilities offered include lobbyists, receptionists, restaurants, employee rooms, gyms, kitchens, per-type rooms, meeting rooms, and employee lockers. To improve the visitor experience, an interior redesign with the theme